The Potential Of Mollusca Communities In Seagrass Ecosystems On Buntal Island Waters West Seram Regency, Maluku Province - Masudin Sangaji; Mahriyana Hulopi; Jacqueline M.F Sahetapy; Nur Tasmiah Sirajuddin; Frijona F. Lokollo; Febrianti Lestari (International Journal of Science and Environment (IJSE), 2023)
Molluscs, especially bivalves and gastropods, make an important contribution to the formation of food chains in seagrass ecosystems. In addition, bivalves and gastropods are often used as biological indicators of aquatic environmental quality in seagrass ecosystems. The close relationship between seagrass beds, bivalves and gastropods can be seen in the expanse of seagrass ecosystems found on Buntal Island which is located in Kotania Bay, West Seram Regency. The potential of bivalves and gastropods, such as the diversity and community structure found in Buntal Island waters, is very important to study because the information is limited. This study aims to determine the diversity of bivalves and gastropods in the seagrass ecosystem of Buntal Island and to determine the community structure of bivalves and gastropods which include; density and relative density, abundance and relative abundance, and frequency of presence and relative frequency of presence. The research method used is quantitative. The results of the analysis of the potential of molluscs showed that the diversity of the composition of mollusc taxa found in seagrass ecosystems on Buntal Island was divided into 2 classes, 25 families, 37 genera, 52 species with a total of 3291 individuals. The mollusc with the highest score in terms of density, abundance, and frequency of presence belonged to Nassarius globossus.